Impact of Orthodontic Space Management on the Success of Implant-sup ported Prosthesis (Academia Journal of Medicine, 2025)
One of the most important clinical decision-making areas is still the treatment of missing teeth using implant-supported prostheses and orthodontic space closure. Recent data shows that both approaches, when properly chosen, produce positive results. Treatment precision and predictability have increased thanks to developments in digital planning, TADs, and interdisciplinary approaches. While implants guarantee functional and aesthetic stability in adults, space closure offers biologically conservative solutions for developing patients. Individualised planning based on the patient’s age, occlusion, and aesthetic requirements is essential for long-term success.
Keywords: Orthodontic space management; Implant supported prosthesis; Maxillary lateral incisors; Temporary anchorage devices (TADs); Esthetic and functional outcomes